Slec heuristic for producing initial CB-CTT timetable - Alsheikh, Noor Nabeel Hazim; Wahid, Juliana (2019)
The use of single graph heuristic ordering of the courses in Curriculum Based Course Timetabling (CB-CTT) in the assigning process of the courses into timetable was unable to achieve feasible initial timetable for all data instances. In addition, some combination of graph heuristic ordering of the courses produce higher cost of feasible initial timetable. This happened because of the unassigned courses (course that unsuccesfull to be be assigned in the timetable in the first round) have limited available slots (least saturated) compared to overall slots. Because of this limited available slots, the possibility of assigning these courses into timetable is not guaranteed. This study proposed on combining the minimum number of available periods (least saturated) with highest number of lectures for courses (SLEC). In SLEC heuristic ordering, when more than one course id have the same number of available slots, these courses then will be ordered by the largest number of lectures. In this study, after assigning courses to the timetable based on SLEC heuristic ordering, the number of unassigned courses for all of the data instances become smaller. In another word, more courses are being assigned into the timetable and the cost of initial timetable should be reduced.